2021
DOI: 10.18573/jcads.61
|View full text |Cite
|
Sign up to set email alerts
|

A corpus analysis of online news comments using the Appraisal framework

Abstract: We present detailed analyses of the distribution of Appraisal categories (Martin & White, 2005) in a corpus of online news comments. The corpus consists of just over one thousand comments posted in response to a variety of opinion pieces on the website of the Canadian English-language newspaper The Globe and Mail. We annotated all the comments with labels corresponding to different categories of the Appraisal framework. Analyses of the annotations show that comments are overwhelmingly negative and that they fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Twitter users tended to express their opinions on global warming through Appreciation (evaluating things), and Judgement (evaluating people's behaviours), rather than directly expressing their emotions through Affect. As Cavasso and Taboada (2021) put it, "strong emotional content is couched in terms of Judgement and Appreciation" (p. 27). Put another way, the results suggested that language users produce sentences like "Global warming is real/disaster" or "It's crazy that ignorant people just don't believe in global warming" rather than "I'm angry/worried about global warming".…”
Section: Discussionmentioning
confidence: 99%
“…Twitter users tended to express their opinions on global warming through Appreciation (evaluating things), and Judgement (evaluating people's behaviours), rather than directly expressing their emotions through Affect. As Cavasso and Taboada (2021) put it, "strong emotional content is couched in terms of Judgement and Appreciation" (p. 27). Put another way, the results suggested that language users produce sentences like "Global warming is real/disaster" or "It's crazy that ignorant people just don't believe in global warming" rather than "I'm angry/worried about global warming".…”
Section: Discussionmentioning
confidence: 99%
“…The term cluster refers to the local groupings of items, be they words, sounds, images or video frames. Then emphasis was given to minimality and contextuality, as described by Cavasso and Taboada (2021). 'The principle of minimality means that the item to be annotated (cluster-span) should be as short as possible, while at the same time including all the words that convey Attitude.…”
Section: Methodsmentioning
confidence: 99%
“…Appraisal Theory deals with how evaluative language aligns readers according to common values and attitudes. Since 2005, Appraisal has been used to: analyse static multimodal texts (Economou 2009, Swain 2012, Mills & Stone et al 2020; it has also been applied to online discourse (language) and combined with corpus techniques (Cavasso & Taboada 2021, Drasovean & Tagg 2015; recently a model has also been proposed for paralanguage that incorporates Appraisal (Martin & Zappavigna 2019;Ngo, Hood et al 2021). To the best knowledge of this researcher, no studies have dealt with a multimodal discourse Appraisal analysis of a corpus of online texts.…”
Section: Introductionmentioning
confidence: 99%
“…This description is also in line with our other recent analyses. Ehret and Taboada (2020) compared online news comments to traditional written and spoken registers and found that they are strongly evaluative in nature, combining argumentative, informational, and some involved features (Ehret and Taboada, 2020, 23), while Cavasso and Taboada (2021) observe their overwhelmingly negative nature, with personal affective opinion (I hate the candidate) eschewed in favour of more detached evaluation (The candidate is incompetent; The candidate's policies are bad). As illustrated in (4), online news comments can thus range from involvedevaluative to involved-argumentative and informationalargumentative.…”
Section: Online News Comments Compared To Other Online Registersmentioning
confidence: 99%